Pengaruh Perilaku Konsumen Masyarakat Kabupaten Gresik Terhadap Penggunaan E-Money - Fanani, Ahmad Faizal; Aji, Tony Seno (Universitas Negeri Surabaya, 2023)
This study aims to identify the influence of cultural, social, personal, and psychological factors on the decision to use e-money in Gresik Regency. E-money can be defined as a